Heat transfer analysis and on-site performance of a curling venue using double ethylene tetra fluoro ethylene (ETFE) cushion structure - Li, L.; Lin, W.; Zhang, T.; Liu, X. (Journal of Building Engineering, 2020)
Thermal environment is quite important for many modern ice competition venues. Maintaining a stable ice pad satisfying requirement usually consumes high energy consumption for refrigeration in curling competition. In this paper, a curling venue with ethylene tetra fluoro ethylene (ETFE) membrane structure is taken as an example to analyze the ice making load of the curling ground. Field tests for thermal environment are carried out in this venue in winter. The sources of ice making load are determined and possible reducing approaches are proposed to lower the energy consumption for ice making issue. It's indicated that average ice making load of the curling ice is 156 W/m2, among which long wave radiation contributes 55.5%. The ceiling temperature could reach 26°C, contributing more than 70% of the longwave radiation. As the view factor between audience and ice surface is quite limited, the interaction is not obvious. It's also noted that cavity ventilation could be a special method to lower the roof temperature on basis of avoiding condensation, reducing the ice making load by 7% for this special building with ETFE membrane envelope. It's hoped that the current research will be beneficial for the design and operation of an ice competition circumstance.